VALIDASI LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS MULTIPLE INTELLIGENCES - Solihah, Ai; Habibie, Muhammad Tri; Kamali, Asep Saefullah (LPPM Universitas Bina Bangsa, 2023)
This study aims to develop LKPD based on Multiplate Intelligences on the material of the Two-Variable Linear Equation System (SPLDV) which is suitable for use in learning activities for class VIII students of junior high school. Multiplate Intelligences-based learning is a learning theory where students can develop various intelligences together to support the learning process, especially mathematics. This research is a type of development research (Research & Development). Based on the results of research and development of LKPD based on Multiplate Intelligences, the validation results were obtained from three experts in their fields, namely mathematicians 83.08% with very suitable criteria, 86.16% learning method experts with appropriate criteria and 83.08% language experts with feasible criteria. So it can be concluded that the development of LKPD based on Multiplate Intelligences on SPLDV material for use in class VIII junior high school students is very valid and feasible for later use in learning